Gendering antifascism : women's activism in Argentina and the world, 1918-1947 - Deutsch, Sandra McGee, 1950- (Pitt Latin American series., 2023)
"Argentine women's long resistance to extreme rightists, tyranny, and militarism culminated in the Junta de la Victoria, or Victory Board, a group that organized in the aftermath of the German invasion of the Soviet Union in defiance of the neutralist and Axis-leaning government in Argentina. A sewing and knitting group that provided garments and supplies for the Allied armies in World War II, the Junta de la Victoria was a politically minded association that mobilized women in the fight against fascism. Without explicitly characterizing itself as feminist, the organization promoted women's political rights and visibility and attracted forty-five thousand members. The Junta ushered diverse constituencies of Argentine women into political involvement in an unprecedented experiment in pluralism, coalition-building, and political struggle. Sandra McGee Deutsch uses this internationally minded but local group to examine larger questions surrounding the global conflict between democracy and fascism"--